Inclusive education in the opinion of the teachers from special pre-schools, regarding the chances of success of the inclusive actions towards particular groups of students, education participants, and teachers’ seniority - CHRZANOWSKA, IWONA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Iwona Chrzanowska, Inclusive education in the opinion of the teachers from special pre-schools, regarding the chances of success of the inclusive actions towards particular groups of students, education participants, and teachers’ seniority. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 127-149. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.06 Within the context of the implementation of the inclusive education model, it seems important to learn the opinions of the teachers, particularly those teachers that are experienced in working with a child/student with a disability, regarding the chances of success of inclusive actions, both in the context of the type, and the level of severity of the developmental disorder, the hazard of the developmental disorder, as well as, regarding the remaining participants of inclusive education, i.e. students without or with special educational needs, however, displaying certain aptitudes. The text focuses on the teacher from the pre-school level of education, as well as, refers to the determination of their attitudes towards the realisation of the model of inclusive education, as related to their seniority.